Decrease in 14-3-3η protein levels is correlated with improvement in disease activity in patients with rheumatoid arthritis treated with Tofacitinib. (March 2019) - Shovman, O.; Gilburd, B.; Watad, A.; Amital, H.; Langevitz, P.; Bragazzi, N.L.; Adawi, M.; Perez, D.; Lidar, M.; Katz, I.; Blank, M.; Biln, N.K.; et al.
Graphical abstract: Abstract: 14-3-3η protein is a proinflammatory mediator that may represent a novel diagnostic and prognostic biomarker for rheumatoid arthritis (RA). We assessed the correlation between changes in serum 14-3-3η levels and changes in clinical disease activity measures in RA patients treated with Tofacitinib (TOF). Paired serum samples from 35 patients with RA were obtained at baseline and 5 months after the initiation of treatment with TOF. The levels of 14-3-3η were measured by JOINT stat 14-3-3η ELISA test kits (Augurex Life Sciences Corp.). The cut-off was defined as 0.19 ng/ml. 14-3-3η positivity was found in 57% of the patients at baseline and in 37% of the patients after 5 months of treatment. Mean ± SD baseline 14-3-3η levels [4.92 ± 8.86 ng/ml] were significantly higher (p < 0.005) than 14-3-3η levels following treatment [1.97 ± 4.59 ng/ml]. A statistically significant improvement (p < 0.001) of CDAI, SDAI, DAS4ESR and DAS4CRP was achieved after 5 month of treatment. Decrease in 14-3-3η protein levels was highly correlated with improvement in DAS4ESR (r = 0.50, p < 0.01), DAS4CRP (r = 0.46, p < 0.01) and ESR (r = 0.36, p = 0.03) and moderately correlated with improvement in CDAI (r = 0.32, p = 0.065) and SDAI (r = 0.33, p = 0.051). The correlation between decrease in 14-3-3η levels and improvement in DAS4ESR remained significant in a partial correlation analysis controlling for ESR (r = 0.39, p = 0.02). This study demonstrates that in RA patients who were treated with TOF, decrease in 14-3-3η levels is correlated with improvement in clinical disease activity parameters. The 14-3-3η protein may serve as an objective biomarker for monitoring of TOF therapy response.